Towards reliable electronic exam networks. (30th March 2022) - El-Gburi, Jabbar; Srivastava, Gautam; Mohan, Senthilkumar
In today's world, stable systems are what everyone is seeking. Furthermore, traits people desire in any system are trust, guarantees of security and fairness. Electronic exams should be considered as the hardest to defy to maintain trust in their relevance. Examination procedures concern any educational organisation which leads to various security techniques being utilised in order to maintain a minimum required level of security. In this paper, we present a secure e-exam network system that performs several processes such as evaluation, and management where all components are in a digital layout. We present a cryptographic platform that should be considered to obtain the required security standards of any educational institution for exam administering networks.